Kemunduran dan Kehancuran Kerajaan Mughal - M. Djamaluddin Miri (el Harakah: Jurnal Budaya Islam, 2009)
Mughal was one of the Islamic Kingdoms that stay long for about 342 years, starting from Sultan Zahr al-Din Muhammad (1483—1530 A.D) until Sultan Siraj al-Din Bahadur Syah (1837—1858 A.D). There are two prominent factors which caused the Kingdom of Mughal separated each other and faced the decrease, internal and external factors. Internally, the Kingdom of Mughal faced the decrease because of no system and mechanism on power succession, and also the lack leadership integrity of the next generation who descended the former leaders. The hedonism life style also became the main cause of the complicated political situation on the Kingdom. Moreover, the political policy which tends to be more puritanical and ideological also ruined the governmental system. Those internal factors, then, caused weak political control and powerless authority of the Kingdom in front of other kingdoms. As a consequence, many rebellions happened everywhere. It absolutely made the power of the Kingdom one by one belongs to other kingdoms. Mughal adalah salah satu Kerajaan Islam yang tinggal sekitar 342 tahun, mulai dari Sultan Zahruddin Muhammad (1483-1530 M) sampai Sultan Sirajuddin Bahadur Syah (1837-1858 M). Ada dua faktor penting yang menyebabkan Kerajaan Mughal berpisah dan menghadapi kemunduran, faktor internal dan eksternal. Secara internal, Kerajaan Mughal menghadapi kemunduran karena tidak ada sistem dan mekanisme suksesi kekuasaan, dan juga kurangnya integritas kepemimpinan generasi berikutnya. Gaya hidup hedonisme juga menjadi penyebab utama situasi politik yang rumit di Kerajaan. Apalagi, kebijakan politik yang cenderung lebih puritan dan ideologis juga merusak sistem pemerintahan. Faktor internal tersebut kemudian menyebabkan lemahnya kontrol politik dan kekuasaan Kerajaan yang tidak berdaya di depan kerajaan lainnya. Akibatnya, banyak pemberontakan terjadi di mana-mana. Itu benar-benar membuat kekuatan Kerajaan satu demi satu menjadi milik kerajaan lain.